PENGARUH PEMANFAATAN LIMBAH TEMPURUNG KELAPA MENJADI ARANG TEMPURUNG TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KALONGAN KABUPATEN KEPULAUAN TALAUD - Adeleida Joroh; Martine Lapod; rolyke Tulangow (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2021)
The purpose of this research is how the effect of utilizing coconut shell waste into coconut shell charcoal on the welfare of the community in Kalongan Village, Talaud Island Tegency. The Type of research conducted by the current researcher is quantitive research which aims to test the established hypotesis. The research location is ini Kalongan Village, Kalongan sub-district, Talaud archipelago district. The population in this study is the village community of kalongan the authors only took 30 samples from people who made use of shell waste into shell charcoal. The data used in this study is primary data so the researcher will take data using a quistionnaire. The Collected data will be analyzed using statistics to the test the proposed hypothesis. The data analysis technique used is simple regression analysis using computer assistance with the SPSS program. From the results of the analysis, it is found that use of shells into shell charcoal had a positive effect on the welfare of the community, this is evidenced by the t-count value of 7.112 while the t-table is 2.048 and the significance value is 0.05. in this case t-count > from t-table 7.112> 2.048. it can be interpreted that the hypothesis is accepted by proving the figure above that t-count is greater than t-table. in other words, the utilization of shell waste into shell charcola have an effect in people's welfare.